2009
DOI: 10.1017/s0007114508184665
|View full text |Cite
|
Sign up to set email alerts
|

Impact of nutritional status at the onset of elementary school on academic aptitude test achievement at the end of high school in a multicausal approach

Abstract: Like in many other countries, few investigations have been carried out in Chile to measure the long-term effects of nutritional status at an early age on scholastic achievement in a multicausal approach. The objectives of the present study were to describe the impact of nutritional, intellectual, family, educational and socio-economic variables at the onset of elementary school in 1987 that may affect achievement on the academic aptitude test (AAT) taken in 1998 at the end of high school, and to quantify the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 56 publications
0
24
0
Order By: Relevance
“…A report on children of Mauritius revealed that malnutrition at three years of age resulted in poor cognitive performance at 11 years of age, which signifies the impact of long-term poverty on children’s foundations [ 65 ]. A study done in Spain showed that children from low socioeconomic classes often experience low IQ and poor academic performance [ 66 ] and possess low scholastic achievement compared to medium or high SES children [ 67 ]. In the same way, SES is associated with physical fitness, cognitive, and socio-emotional outcomes in children in the US [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…A report on children of Mauritius revealed that malnutrition at three years of age resulted in poor cognitive performance at 11 years of age, which signifies the impact of long-term poverty on children’s foundations [ 65 ]. A study done in Spain showed that children from low socioeconomic classes often experience low IQ and poor academic performance [ 66 ] and possess low scholastic achievement compared to medium or high SES children [ 67 ]. In the same way, SES is associated with physical fitness, cognitive, and socio-emotional outcomes in children in the US [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…This correlation was also observed in the current study, although a weak positive correlation exists between anthropometric measures such as weight and mid-upper arm circumference and psychomotor scores. Children who may have missed the critical window of opportunity for brain development may exhibit lower cognitive and psychomotor skills [ 13 ]. Though it is a limitation in the study, the extent of missed cognition and psychomotor skills may require a more individualized approach which may also include activities that may stimulate brain development alongside nutrition [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Valenzuela 49,52 found a significant association between malnutrition and low maternal sensitivity and a high risk of developing an anxious mother-child attachment in low-income families. Other results indicated that recovery from the cognitive and physical effects of malnutrition was better in children who grew up with their biological parents than in institutionalized children 39,45 . In a study conducted to reveal the variables associated with stunted growth in school children, Amigo et al 50 showed that environmental factors, such as paternal alcoholism, lack of good health care, poor hygiene, malnutrition, and a short breastfeeding period, were factors contributing to stunted growth.…”
Section: Childcare In the Nineteenth Century: Foundling Homesmentioning
confidence: 99%